Classification ofpotato germoplasm (solanum tuberosum subsp. tuberosum) by quality parameters for industry process (2001)
With the great existent variability in Colombia of the specieSolanum tuberosum L. it is indispensable to carry out processesof genetic improvement for not wasting this great resource. Eighty two varieties of the Colombian Central Collection of Solanum tuberosum subsp. tuberosum were used for determining variables related with its processing capacity in the food industry. Making use ofthe correlation analysis and multivariate statistics (Principal components and cluster analysis) potato accessions were identified because of their high capacity of being used as progenitors in obtaining genotypes with desirable traits for the fried potato industry.